RUANG KOMUNITAS SENIOR: HORIZON - Monique Priscilla; Petrus Rudi Kasimun (Jurusan Arsitektur dan Perencanaan, 2021)
Globally, elderly population keeps increasing in numbers. Since 2015, Asian countries including Indonesia began entering ageing population. Humankind predicted to live longer. Nonetheless, they are mortal. Humankind is called Dasein (being in the world). The world is a concept, relationship between ourselves and objects or other human beings. Basically Dasein is actively involved with everyday objects. The essence of Dasein is it's active interpreting (constantly something to be settled) seeing as Dasein cannot be considered a finished whole, Dasein always looking for identity. Dasein’s being as a whole can only be disclosed by Dasein being dead, for they no longer exist in the world. According to 2005 Stanford research, the majority of elderly prefer contributing to society, and 30% proven to do so. The latest stage of man emotional development experienced by elderly, individually older than the age 60. Interacting with the younger generation would result in greater contentment and benefits each other. By providing a space to encounter other people with different ages, hopefully there will be exchange of experience, a legacy of life. Through the Horizon Senior Society, millennial generations can explore a dwelling story from the past to the present and the future. Keywords: Elderly; Death; Interaction; Dwelling. Abstrak Secara global, populasi lansia diprediksi terus mengalami peningkatan. Sejak tahun 2015 Benua Asia dan Indonesia memasuki era penduduk menua. Diprediksi manusia akan hidup lebih lama lagi. Manusia disebut sebagai Dasein (Ada-di-sana), yakni Ada-dalam-dunia (being-in-the-world). Dunia merupakan konsep dimensi hubungan antar diri sendiri dengan benda atau manusia lain. Dasein pada dasarnya terlibat secara aktif dengan objek keseharian. Esensi Dasein adalah suatu 'kebeluman terus menerus' karena ia tidak pernah mencapai keseluruhannya, selalu mewujudkan dan mencari jati diri. Manusia mencapai totalitasnya dalam kematian, karena manusia/dasein berhenti sebagai berada-di-dalam-dunia. Menurut riset Stanford tahun 2005, mayoritas lansia memilih untuk berkontribusi terhadap masyarakat, dan terbukti 30% sudah menjalaninya. Tahap akhir pengembangan emosi manusia dirasakan pada lansia umur 60 tahun ke atas. Berinteraksi dengan generasi muda akan memberi dampak rasa kepuasan yang lebih besar dan saling menguntungkan. Dengan memberikan wadah sebagai titik temu antar generasi, diharapkan terjadi sebuah transfer pengalaman akan legacy kehidupan. Melalui Horizon Senior Society, generasi milenial dapat menggali sebuah cerita dwelling masa lalu, ke masa kini dan masa depan.